2009
DOI: 10.1161/circulationaha.108.844779
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Occlusion Does Not Eliminate the Need for Warfarin

Abstract: A trial fibrillation (AF) is the most common sustained heart rhythm disorder. It is increasing in incidence, which has major societal implications for our aging population. [1][2][3] It is estimated to affect 1% to 1.5% of the developed world, and the incidence increases with age to a rate of 19.2 per 1000 patient-years in those 65 years of age and older. The most important aspect of the treatment of patients with AF is the prevention of stroke. The average annual stroke rate across risk groups is 5%, and AF-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 46 publications
2
46
0
4
Order By: Relevance
“…It has been postulated that residual leaks may be a risk for thrombi formation and embolic events in patients with partially occluded LAAs, therefore leading to the need of continued anticoagulation therapy. 28,29 This suggests that among AF patients with nondilated and elliptical LAA orifice, devices may need to be elliptical to adequately occlude the LAA orifice.…”
Section: Impact Of Presence and Type Of Af On Laa Dimensionmentioning
confidence: 99%
“…It has been postulated that residual leaks may be a risk for thrombi formation and embolic events in patients with partially occluded LAAs, therefore leading to the need of continued anticoagulation therapy. 28,29 This suggests that among AF patients with nondilated and elliptical LAA orifice, devices may need to be elliptical to adequately occlude the LAA orifice.…”
Section: Impact Of Presence and Type Of Af On Laa Dimensionmentioning
confidence: 99%
“…With this information, clinicians could optimize medical therapy for stroke risk factors such as hypertension, 10,11 improve the evidence-based use of oral anticoagulation in patients with atrial fibrillation and evaluate intraoperative surgical strategies (e.g., removal of the left atrial appendage 12 ) in patients whose clinical characteristics predict an increased risk of stroke. We examined the rate and predictors of long-term stroke within 2 years after cardiac surgery.…”
mentioning
confidence: 99%
“…Whitlock et al suggested a local approach might be insufficient to prevent the systemic prothrombotic state, which increases the chance of thrombosis and embolism from multiple sources in addition to the LAA, such as the aorta, the LV and the cerebral vasculature. 29 Because the efficacy of LAA closure for stroke prevention in AF will depend on the patient's background, clinicians have to evaluate LV function, presence of patent foramen ovale, disorders of coagulation, or underlying disease that could lead to atherosclerotic changes and modification of the bleeding risk. However, this new technique is an emerging and viable clinical strategy for stroke prevention in AF patients, and should be considered as an alternative for patients who have contraindications for, or have been ineffectively treated with, OACs.…”
Section: Discussionmentioning
confidence: 99%